Catch pattern and size selectivity for a gear designed to prevent fish injuries during the capture process in a North-East Atlantic demersal trawl fishery - Herrmann, Bent; Sistiaga, Manu; Larsen, Roger B.; Brinkhof, Jesse; Gjøsund, Svein Helge; Jacques, Nadine; Santos, Juan (Regional Studies in Marine Science, 2020)
In the North-East Atlantic demersal trawl fishery targeting cod and haddock, the interest on fishing gear designs that preserve fish quality and welfare has grown. However, the gear configurations tested so far imply practical challenges, therefore, more user-friendly designs are still sought by the industry. For a new design to be considered, it needs to have size selective properties that are at least comparable to those obtained with the standard grid and codend gear configuration used in the fishery today. In the present study, we investigated the size selectivity of a new design on three of the most important commercial species in the fishery: cod ( Gadus morhua ), haddock ( Melanogrammus aeglefinnus ) and redfish ( Sebastes spp. ). The new design did not include a sorting grid and was composed of a large mesh segment followed by a quality preserving codend installed in the aft of the gear. The results showed that the experimental gear did not work as intended, catching significantly higher numbers of undersized fish than the standard gear for all three species included in the study. Further, based on hypothesis testing, the null hypothesis of “zero release from the experimental gear” could not be falsified, meaning that it could not be ruled out that there was no escape of fish at all from the experimental gear tested. Despite the negative results obtained, the results from this study enhance the understanding of gear selectivity in towed fishing gears.